Factors affecting students’ concept retention in learning science online using instructional videos - Aguanta, Catherine B.; Augusto, Margery Anne T.; Bajenting, Jonajean V.; Buayaban, Katrina Claire; Cruz, El Jane P.; Fantonial, Niña Faith; Kwan, Jane Aubrey M.; Legaspino, Jimmoy; Acut, Dharel P.; Picardal, Marchee T. (Intelektual Pustaka Media Utama, 2024)
Effective science instruction in a blended learning approach is synonymous with the strategic use of instructional videos (IVs) to fill the gap in teacher support. This study aims to determine the IVs’ effectiveness in improving students' concept retention and overall learning experiences. The experimental group was exposed to instruction integrating IVs via embedded mixed-method design, whereas the control group was exposed to traditional lecture methods. The results showed that students' post-test scores and concept retention improved significantly in the experimental group, where students reported better learning experiences than in the control group. This beneficial effect of a technology-integrated approach can be attributed to various elements of IVs, such as engaging content, motion graphics, video length, the language used, and the speaker's perspective. This study recommends that IVs be used to enhance learning opportunities and results in the teaching and learning process.